Identification of a window for quiescent H-mode operation in MHD stability diagram of DIII-D plasmas - N. Aiba; X. Chen; T.H. Osborne; K.H. Burrell (Nuclear Fusion)
A window for quiescent H-mode (QH-mode) operation in DIII-D plasmas in the diagram of pedestal magnetohydrodynamic (MHD) stability was identified through linear MHD stability analysis, accounting for the effects of plasma rotation and ion diamagnetic drift. The operation window lies between the stability boundaries of the kink/peeling mode (K/PM) identified with and without the inclusion of plasma rotation effects. In this region, the mode remains unstable unless rotation effects are considered alongside the ion diamagnetic drift, which is consistently included in the analysis. The stabilization of the MHD mode, facilitated by the coupled effects of plasma rotation and ion diamagnetic drift, plays a crucial role in widening the window, enabling the attainment of the QH-mode state. Furthermore, the suppression of edge localized modes (ELM) can be achieved by controlling the pedestal structure to ensure the plasma state remains within the operation window. The location of the operation window in the stability diagram depends on the K/PM stability properties. Therefore, optimizing conditions for QH-mode requires adjustments based on changes in stability characteristics. A pressure pedestal and its associated bootstrap current density near the last closed flux surface are advantageous for situating the plasma state within the window. However, excessive current density can trigger ELMs. This trend was confirmed through comparisons of MHD stability diagrams between QH-mode and ELMy H-mode plasmas.